An Overview on Design Parameters of Practical Lithium‐Ion Capacitors. Issue 5 (25th January 2021) - Jin, Liming; Yuan, Jianmin; Shellikeri, Annadanesh; Naderi, Roya; Qin, Nan; Lu, Yanyan; Fan, Runlin; Wu, Qiang; Zheng, Junsheng; Zhang, Cunman; Zheng, Jim P.
Abstract: Lithium‐ion capacitors (LICs), composed of a lithium ion battery (LIB)‐type electrode and an electrochemical capacitor (EC)‐type electrode (non‐Faradic), operating in a lithium ion‐containing electrolyte, have the potential to deliver high energy density, high power density and long cycle life simultaneously. In this minireview, we focus on the development of practical LICs, which has been barely introduced in previous reviews, to supplement their development course. This minireview includes the introduction of fundamentals, analysis of the key parameters, and review of the key technologies of practical LIC systems. The practical LIC technologies have been summarized and discussed in contrast to the commercial ECs. Finally, we propose the future research for LICs in terms of materials and their properties, which aims to provide guidelines for the researchers in the fields of LICs. Abstract : From theory to practice : In this minireview, we focus on the development of practical lithium‐ion capacitors, which has been scarcely introduced in previous reviews, to supplement their development cycle. This minireview includes the introduction of fundamentals, analysis of the key parameters, and review of the key technologies of practical LIC systems.